2004
DOI: 10.1002/nag.364
|View full text |Cite
|
Sign up to set email alerts
|

Size effect on fracture energy induced by non‐locality

Abstract: SUMMARYExperimental results available in the literature indicate that the nominal fracture energy of concrete (defined as total work of fracture divided by the ligament area) depends on the size of the specimen. Theoretical modelling of the size effect on nominal fracture energy based on a non-local constitutive model is attempted in this paper. The influence of various details of the integral-type non-local formulation, e.g. of the specific form of non-local averaging in the vicinity of a physical boundary, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 15 publications
1
47
0
1
Order By: Relevance
“…Such results, showing a great sensitivity of the mechanical response of specimens to the weight function, have already been pointed out, e.g. by Jirasek and coworkers [13].…”
Section: Size Effect On Notched Specimenssupporting
confidence: 64%
“…Such results, showing a great sensitivity of the mechanical response of specimens to the weight function, have already been pointed out, e.g. by Jirasek and coworkers [13].…”
Section: Size Effect On Notched Specimenssupporting
confidence: 64%
“…As the first bracketed terms in (37) and (38) are positive when loading takes place, their elimination in the above expressions is straightforward. We can now rewrite the damage criteria in their final forms…”
Section: Damage Functionsmentioning
confidence: 98%
“…The calibration process for all model parameters is based on uniaxial tensile and compressive tests. This requirement has been widely accepted and adopted because of its simplicity (see [7,14,[34][35][36][37]). …”
Section: Introductionmentioning
confidence: 99%
“…These observations can see some similarities with the ones made by Figure 12: Crack field at 50% of the peak load for the original nonlocal method a) and the stress based nonlocal method b). (Jirásek et al 2004). Indeed, they observed that the better way to describe size effect on fracture energy for notched beams in an original nonlocal continuous framework was to replace the explicit description of the notch by a fully damage area.…”
Section: Crack Analysis At Failurementioning
confidence: 99%
“…Indeed, by introducing an internal length in the modeling, the size of the FPZ is explicitly defined. (Simone et al 2004) and (Jirásek et al 2004) for the description of size effect, have pointed out the problematic of the description of the nonlocal interactions in the vicinity of a notch tip. To address the description of size effect for notched beams under three-point bending loading, this problem is of main concern as the FPZ develop in this area at peak load.…”
Section: Introductionmentioning
confidence: 99%